Is psychologically vulnerable rural-to-urban migrants' mental health further at stake under China's tightened COVID-19 measures: how should the government respond? - Hung, Jason (Frontiers in Sociology, 2023)
There is a well-documented scholarly discourse on how the COVID-19 outbreak adversely affects the mental health of Chinese nationals. However, there is little evidence revealing how the public health crisis negatively influenced the mental health of rural-to-urban migrants in China. The relevant literature argues that rural-to-urban migrant workers and their dependents have been experiencing discrimination, exclusion, and stigmatisation in the urban labour market and social space, thereby jeopardising their mental health to a large extent. However, whether the COVID-19 outbreak and its associated consequences further compounded rural-to-urban migrant workers’ mental health has rarely been discussed. Since 2010, the Chinese government has emphasised the importance of promoting positive mental health. Without identifying how COVID-19 specifically imposed mental health challenges on rural-to-urban migrant cohorts, Chinese policymakers cannot effectively and efficiently address the dilemmas faced by such vulnerable groups. The significant rural-to-urban migrant population (i.e. 291 million), alongside their disposition to encounter social and psychological challenges, prompts the urgency to develop this narrative essay to examine whether their mental health burdens worsened during the pandemic. The author also discusses remedies for the worsened mental issues faced by migrant cohorts, and recommends policies that local Chinese governments should adopt to mitigate the mental health burdens encountered by rural-to-urban migrants.